WJMSC‐derived small extracellular vesicle enhance T cell suppression through PD‐L1. Issue 4 (8th February 2021) - Li, Meizhang; Soder, Rupal; Abhyankar, Sunil; Abdelhakim, Haitham; Braun, Mitchell W.; Trinidad, Camille V.; Pathak, Harsh B.; Pessetto, Ziyan; Deighan, Clayton; Ganguly, Siddhartha; Dawn, Buddhadeb; McGuirk, Joseph; et al.
Abstract: Both mesenchymal stem cells (MSCs) and their corresponding small extracellular vesicles (sEVs, commonly referred to as exosomes) share similar immunomodulatory properties that are potentially beneficial for the treatment of acute graft versus host disease (aGvHD). We report that clinical grade Wharton's Jelly‐derived MSCs (WJMSCs) secrete sEVs enriched in programmed death‐ligand 1 (PD‐L1), an essential ligand for an inhibitory immune checkpoint. A rapid increase in circulating sEV‐associated PD‐L1 was observed in patients with aGvHD and was directly associated with the infusion time of clinical grade WJMSCs. In addition, in vitro inhibitory antibody mediated blocking of sEV‐associated PD‐L1 restored T cell activation (TCA), suggesting a functional inhibitory role of sEVs‐PD‐L1. PD‐L1‐deficient sEVs isolated from WJMSCs following CRISPR‐Cas9 gene editing fail to inhibit TCA. Furthermore, we found that PD‐L1 is essential for WJMSC‐derived sEVs to modulate T cell receptors (TCRs). Our study reveals an important mechanism by which therapeutic WJMSCs modulate TCR‐mediated TCA through sEVs or sEV‐carried immune checkpoints. In addition, our clinical data suggest that sEV‐associated PD‐L1 may be not only useful in predicting the outcomes from WJMSC clinical administration, but also in developing cell‐independent therapy for aGvHD patients.